Unfold studio: supporting critical literacies of text and code. Issue 5 (8th May 2019) - Proctor, Chris; Blikstein, Paulo
Abstract : Purpose: This research aims to explore how textual literacy and computational literacy can support each other and combine to create literacies with new critical possibilities. It describes the development of a Web application for interactive storytelling and analyzes how its use in a high-school classroom supported new rhetorical techniques and critical analysis of gender and race. Design/methodology/approach: Three iterations of design-based research were used to develop a Web application for interactive storytelling, which combines writing with programming. A two-week study in a high-school sociology class was conducted to analyze how the Web application's textual and computational affordances support rhetorical strategies, which in turn support identity authorship and critical possibilities. Findings: The results include a Web application for interactive storytelling and an analytical framework for analyzing how affordances of digital media can support literacy practices with unique critical possibilities. The final study showed how interactive stories can function as critical discourse models, simulations of social realities which support analysis of phenomena such as social positioning and the use of power. Originality/value: Previous work has insufficiently spanned the fields of learning sciences and literacies, respectively emphasizing the mechanisms and the content of literacy practices. In focusing a design-based approach on critical awareness of identity, power and privilege, this research develops tools and theory for supporting critical computational literacies. This research envisions a literacy-based approach to K-12 computer science which could contribute to liberatory education.